Impacts of brewing methods on sensory perception and organoleptic compounds of coffee - Lucas Louzada Pereira; Rogério Carvalho Guarçoni; José Maria Rodrigues da Luz; Alanne Carvalho de Oliveira; Aldemar Polonini Moreli; Cristhiane Altoé Filete; Genilson de Paiva; Danieli Grancieri Debona; Willian dos Santos Gomes; Wilton Soares Cardoso; Sávio da Silva Berilli; Emanuele Catarina da Silva Oliveira (Food Chemistry Advances, 2023)
Coffee beverage presents unique organoleptic characteristics of aroma and taste. These sensory attributes depend on the chemical composition of the brewed coffee. Our objectives were to determine the sensory quality of the coffee beverage obtained by different brewing methods as assessed by untrained tasters and to characterize the solid residues of this extraction using the medium infrared spectrum. Four brewing methods were evaluated by 124 untrained consumers. The infusion method presented better global impression and preference of these consumers than the other brewing methods. Significant changes in the chemical composition of the coffee residues were observed. These changes influenced the acceptance of the consumers and can be due to the potential of retention or filtering of organic compounds by the brewing method. Thus, there was a sensory quality difference among the brewing methods and the infrared spectrum indicated the need to distinguish the classes of organic compounds for a better understanding of how coffee brewing interacts with the chemical composition.